Addressing reproductive health needs across the life course: an integrated, community-based model combining contraception and preconception care. (January 2023) - Hall, Jennifer; Chawla, Mehar; Watson, Daniella; Jacob, Chandni Maria; Schoenaker, Danielle; Connolly, Anne; Barrett, Geraldine; Stephenson, Judith
Summary: Prevention of pregnancy (contraception) and preparation for pregnancy (preconception care) are services that most people need during their reproductive life course. Despite increased attention, and growing recognition that health before pregnancy is crucial to addressing disparities in maternity outcomes, service provision is far from routine. We bring together evidence from the literature, new quantitative and qualitative data on women's preferences, and case studies of existing practice, to develop an integrated, community-based model that synthesises reproductive life planning, contraception, and preconception care. Our model provides a holistic, life course approach, encompassing school-based education, social media, and national campaigns, and highlights the need for training and system-level support for the range of health-care professionals who can deliver it. This high-level model can be adapted across settings, leading to a step change in the provision of preconception care in the community with consequent improvements in health and wellbeing, and reductions in inequalities at population level.